2018
DOI: 10.1016/j.eats.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Technique for Type IV SLAP Lesion Repair

Abstract: Type IV SLAP tears involve bucket-handle tears of the superior labrum with the tears extending into the biceps tendon. Surgical treatment options involve either primary repair or biceps tenodesis. Recent literature has shown good clinical outcomes after subpectoral biceps tenodesis for the treatment of type II and IV SLAP lesions. The purpose of this article is to present our technique for arthroscopic superior labrum repair with suture anchors and open subpectoral biceps tenodesis with an interference screw.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Various fixation techniques and implants are described for subpectoral biceps tenodesis. [15][16][17][18][19] Interference screw fixation has traditionally served as the gold standard with superior biomechanical strength. 15 However, because of concerns for a humeral stress riser with larger drill holes, other techniques have evolved to mitigate this risk while taking advantage of the benefits of the subpectoral location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various fixation techniques and implants are described for subpectoral biceps tenodesis. [15][16][17][18][19] Interference screw fixation has traditionally served as the gold standard with superior biomechanical strength. 15 However, because of concerns for a humeral stress riser with larger drill holes, other techniques have evolved to mitigate this risk while taking advantage of the benefits of the subpectoral location.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on different suprapectoral and subpectoral fixation techniques for biceps tenodesis, showing interference screw fixation to provide the strongest biomechanical stability. [15][16][17][18][19]22 However, complications including implant failure, bioabsorbable screw reactions, and especially humeral fractures have been reported. [12][13][14] Sears et al 14 reported a case series of humeral fractures after subpectoral biceps tenodesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of degenerative multiple fraying of the superior labrum, a biceps tenodesis was preferred (in case of an unstable superior labral tear, an additional SLAP repair was performed, as mentioned below). 1 …”
Section: Methodsmentioning
confidence: 99%
“…The long head of biceps tendon, superior labrum, rotator cuff, cartilage surfaces, and surrounding structures are evaluated thoroughly. 12 Arthroscopic Decompression of the Spinoglenoid Cyst.…”
Section: Diagnostic Arthroscopymentioning
confidence: 99%